Descriptions of two new species of Torodorinae (Lepidoptera, Lecithoceridae), with three new records of Torodora Meyrick from Laos - Park, Kyu-Tek; Bae, Yang-Seop (Zootaxa, 2017)
Two new species of Torodorinae: Caveana plenalinea Park, sp. nov. and Antiochtha hemitatos Park, sp. nov., are described from Laos. At the same time, three species of the genus Torodora are reported for the first time from Laos.